Optimizing continuous passive motion duration following arthroscopic release of elbow contracture: a retrospective study - Xunhao Wang; Qianyuan Liu; Jiyang Tan; Jiani Wu; Haoyu Yang; Fei Xiong; Qiuwen Ying; Jingyi Mi (BMC Musculoskeletal Disorders)
Abstract Background The anatomical structure of the elbow joint makes it vulnerable to contractures. While elbow arthroscopy minimizes soft tissue damage and enhances early rehabilitation, the optimal duration for postoperative Continuous Passive Motion (CPM) therapy is unclear. This retrospective study aims to establish the appropriate duration of CPM following arthroscopic elbow contracture release. Methods We analyzed postoperative outcomes from patients undergoing CPM rehabilitation for 1, 3, or 5 months. Metrics such as ASES, VAS, DASH, MEPS scores, grip strength, and range of motion were assessed before surgery and at 1,3,6 and 12 months post-surgery. Results Patients who received 3 or 5 months of CPM therapy showed statistically significant improvements in elbow flexion-extension, range of motion, and functional scores (ASES, VAS, DASH, MEPS) compared to the 1-month group (p < 0.05). However, no significant differences were observed between the 3- and 5-month groups. Conclusions A 3-month CPM period is effective for patients with higher functional demands, with no additional benefit from extending therapy to 5 months.